Pengaruh Pengetahuan Akuntansi dan Kepribadian Wirausaha Terhadap Kinerja Manajerial Pada Perusahaan Manufaktur Di Provinsi Sumatra Barat - Rizka Rizka; Ethika Ethika; Resti Yulistia M (UNIVERSITAS RAHARJA, 2021)
This study aims to determine the effect of accounting knowledge and entrepreneurial personality on managerial performance in manufacturing companies located in the province of West Sumatra. List of manufacturing companies was obtained from Badan Pusat Statistik (BPS) Padang. Data was collected by survey method. Data obtained using a questionnaire distributed to managers. For the selection of samples was done by purposive sampling method. Analysis using testing through test the validity and reliability of the data, the classical assumption test (test for normality, multicollinearity), multiple linear regression hypothesis test. The study concluded the effect of accounting knowledge and entrepreneurial personality simultaneously influence on managerial performance, but partially entrepreneurial personality has no effect on managerial performance.